2012
DOI: 10.3329/bjvm.v9i1.11217
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Commercial Serodiagnostic Tests for the Seroprevalence Study of Brucellosis in Stray Dogs in Bangladesh

Abstract: A prospective study of Brucella sero-prevalence was conducted in 30 stray dogs in Mymensingh Municipal Corporation area of Bangladesh during the period from January to December 2009. All the sera were screened primarily by Rose Bengal Plate Test (RBPT). Positive, doubtful and negative serum samples were further confirmed with Slow Agglutination Test (SAT), Standard Tube Agglutination Test (STAT) and indirect Enzyme Linked Immunosorbent Assay (ELISA) and all the SAT, STAT and ELISA negative samples were confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The influence of sex in the prevalence of brucellosis has been studied in cattle, small ruminants and wild animals [74,77,79,80,84]. Female ruminants presented a higher odds of brucellosis infection, the same has been observed in female dogs compared to male dogs [85]. Although this is difficult to explain, it could be associated with the intrinsic biology of the microorganisms and its tropism to the foetal tissues as previously described.…”
Section: Sexmentioning
confidence: 84%
“…The influence of sex in the prevalence of brucellosis has been studied in cattle, small ruminants and wild animals [74,77,79,80,84]. Female ruminants presented a higher odds of brucellosis infection, the same has been observed in female dogs compared to male dogs [85]. Although this is difficult to explain, it could be associated with the intrinsic biology of the microorganisms and its tropism to the foetal tissues as previously described.…”
Section: Sexmentioning
confidence: 84%
“…Talukder, Samad and Rahman (2012) conducted a sero-prevalence study on 30 stray dogs from the Mymensingh Municipal Corporation area in Bangladesh. The study revealed that the prevalence of B. canis in younger dogs up to 7 months of age was consistently 0%, while in the older dogs the results were 14.81%, 7.40%, 7.40% and 11.11% using the Rose Bengal plate test (RBPT), serum agglutination test (SAT), TAT and ELISA tests, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent and real prevalences were calculated according to NOORDHUIZEN et al (1997). Apparent prevalence was obtained by dividing the number of seroreactive animals by the total number of animals, while real prevalence was estimated by adjusting the apparent prevalence considering sensitivity (52.94%) and specificity (98.7%) of the diagnosis using the B. canis protocol (KEID et al, 2009), as well as the diagnosis sensitivity (100%) and specificity (96.29%) for infection by B. abortus (TALUKDER et al, 2011) according to this formula:…”
Section: Municipality Residents *mentioning
confidence: 99%